Survei Motivasi Peserta Didik Putri dalam Mengikuti Materi PJOK di SMP Swasta Se Kecamatan Sempu Kabupaten Banyuwangi - Octavia Putri; Usman Wahyudi (Mutiara Pendidikan dan Olahraga, 2025)
in private junior high schools throughout Sempu District, female students follow Physical Education, Sports, and Health (PJOK) learning with feelings of boredom, doubt, and difficulty. However, it is not yet known what level of motivation female students have in following Physical Education, Sports, and Health (PJOK). This study aims to analyze the motivation level of female students in participating in Physical Education, Sports, and Health (PJOK) learning at private junior high schools in Sempu District, Banyuwangi Regency. The research employs a survey method with a descriptive quantitative approach. Data were collected through questionnaires distributed to 62 respondents and analyzed using descriptive statistics with the assistance of SPSS software. The findings indicate that students' motivation in PJOK learning is generally high, with an actual score of 4,637 out of an ideal score of 6,200. The obtained mean score is 3.738, with a Respondent Achievement Level (TCR) of 74.79. Although most indicators reflect a high level of motivation, certain aspects remain in the moderate category, such as indicators X11, X16, X18, and X20. Factors contributing to lower motivation in these aspects may include a lack of variation in teaching methods, limited sports facilities, and insufficient external support. Therefore, efforts to enhance motivation should include more interactive teaching methods, improved sports facilities, and stronger environmental support to further increase students' enthusiasm for PJOK learning.